Pemberian Tablet Fe Dan Jus Jambu Biji Pada Remaja Putri Yang Anemia Defisiensi Besi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Iron deficiency anemia is a decrease in hemoglobin concentration ( 0.05 Conclusion: there was no significant difference in mean hemoglobin levels between the control and treatment groups, however, judging from the average difference between the control group and the treatment occurs trend increase in the average hemoglobin concentration is 0.24. Keywords: Anemia Iron Deficiency, Provision of a Tablets Fe, Provision of a Tablets Fe And Guava Juice